Universal Super‐Resolution Multiplexing by DNA Exchange. Issue 14 (3rd March 2017) - Schueder, Florian; Strauss, Maximilian T.; Hoerl, David; Schnitzbauer, Joerg; Schlichthaerle, Thomas; Strauss, Sebastian; Yin, Peng; Harz, Hartmann; Leonhardt, Heinrich; Jungmann, Ralf
Abstract: Super‐resolution microscopy allows optical imaging below the classical diffraction limit of light with currently up to 20× higher spatial resolution. However, the detection of multiple targets (multiplexing) is still hard to implement and time‐consuming to conduct. Here, we report a straightforward sequential multiplexing approach based on the fast exchange of DNA probes which enables efficient and rapid multiplexed target detection with common super‐resolution techniques such as (d)STORM, STED, and SIM. We assay our approach using DNA origami nanostructures to quantitatively assess labeling, imaging, and washing efficiency. We furthermore demonstrate the applicability of our approach by imaging multiple protein targets in fixed cells. Abstract : Many happy returns : A straightforward sequential multiplexing approach based on the fast exchange of DNA probes has been developed that enables efficient and rapid multiplexed target detection with common super‐resolution techniques such as (d)STORM, STED, and SIM.